Large Displays Enhance Optical Flow Cues and Narrow the Gender Gap in 3D Virtual Navigation - Tan, Desney; Czerwinski, Mary; Robertson, George (Human Factors: The Journal of the Human Factors and Ergonomics Society, 2006)
Existing reports suggest that males signiﬁcantly outperform females in navigating 3-D virtual environments. Although researchers have recognized that this may be attributable to males and females possessing different spatial abilities, most work has attempted to reduce the gender gap by providing more training for females. In this paper, we explore using large displays to narrow the gender gap within these tasks. Background: While evaluating various interaction techniques, we found that large displays affording wider ﬁelds of view seemed to improve virtual navigation performance in general and, additionally, to narrow the gender gap that existed on standard desktop displays. Method:We conducted two experiments (32 and 22 participants) exploring the individual contributions of display and geometric ﬁelds of view to the observed effects as well as isolating factors explaining performance increases seen on the large displays. Results:We show that wider ﬁelds of view on large displays not only increase performance of all users on average but also beneﬁt females to such a degree as to allow them to perform as well as males do. We further demonstrate that these beneﬁts can be attributed to better optical ﬂow cues offered by the large displays. Conclusion:These ﬁndings provide a signiﬁcant contribution, including recommendations for the improved presentation of 3-D environments, backed by empirical data demonstrating performance beneﬁts during navigation tasks. Application. Results can be used to design systems that narrow the gender gap in domains such as teleoperation and virtual environments for entertainment, virtual training, or information visualization.